Het einde der tijden en het Efraïm Genootschap - Hak, Durk; Jansma, Lammert Gosse (Religie & Samenleving, 2010)
The expectation of the end of times is of all times and of all places. Yet, in the various religions the frequency of millennial outbursts fluctuates. In Christianity, the frequency is related to the nature of its soteriology. It is argued that although a post-Calvinist conception of salvation may heighten the belief in millenarian dreams, yet it is highly likely that recruits are members of mainline protestant churches. By means of rational choice–theory it is made plausible which believers will be recruited and under what conditions joining may occur. A particular millennistic group in the Netherlands believing to live in the end of times and expecting to be taken to heaven in 2001, the Efraïm Society led by the prophet Elijah, is taken as a case. The effects of failed prophecy on leadership, on the followers and the doctrine are examined as well.